(untitled) (Research, Society and Development, 2021)
The Angiotensin-Converting Enzyme (ACE) generates angiotensin 2 as a final product, which promotes increased sympathetic activity, but the effects of the different ACE polymorphisms on heart rate variability (HRV) is unclear. The purpose of the present review is to synthesize findings in ACE associations and behavior of HRV in healthy subjects. Pubmed, Web of Science, and Scopus databases were searched without language restriction until January 2021. Original studies that analyzed the association between ACE polymorphisms and HRV in healthy individuals were included and review studies, letters to the editor, editorials and points of view were excluded. As the systematic result identified 548 studies as eligible after application of the methodological descriptors. Following the selection process, the studies were evaluated within the inclusion and exclusion criteria and then, six studies were selected for the present review. Paper’s quality was assessed by Q-Genie and all were considered highest quality. Evidence on the impact of ACE polymorphisms on HRV is not consensual, studies do not clearly demonstrate a pattern of HRV behavior due ACE polymorphisms. Based on limited research number and their conflicting results, it is concluded that there is no possibility to speak causally about the associations between ACE polymorphisms and HRV behavior.